Respectable white ladies, wayward girls, and telephone thieves in Miami’s “Case of the Clinking Brassieres” - Miller, Vivien (2010)
This essay uses the 1950 “case of the clinking brassieres” to explore female theft in Miami at mid-century and the ways in which gender, race, class, respectability, and youth offered protections and shaped treatment within Florida’s criminal justice system. It focuses on the illegal activities of three female telephone employees, their criminal prosecution, and post-conviction relief. These seemingly respectable coin thieves challenged a familiar image of theft as a lower-class crime associated with poverty and economic need, while their blonde hair and white skin (and an idealization of the meanings of white beauty standards), complicated public attitudes in a period when “true” or serious criminals were racketeers and organised crime operatives.